Bedside Shift-to-Shift Handoffs: A Systematic Review of the Literature. Issue 1 (January 2016) - Mardis, Tyler; Mardis, Matt; Davis, Joshua; Justice, Ellen M.; Riley Holdinsky, Stacie; Donnelly, John; Ragozine-Bush, Heather; Riesenberg, Lee Ann
Abstract : Multiple institutions identify communication and shift-to-shift handoffs as a source of clinical errors. Conducting handoffs at the bedside has been proposed as a potential solution to improve the quality of communication at change of shift. This article reports a systematic review of English-language research articles, published between January 1, 2008, and October 31, 2014, focused on bedside shift-to-shift handoffs. Forty-one articles were identified and analyzed in this systematic review. Abstract : Supplemental Digital Content is Available in the Text.